The Effect of Workplace Well-being on Task Performance in Employees: The Mediating Role of Work Engagement - Siswanti, Dian Novita; Daud, Muh; Nugraha, Dwi Yan; Zhalifunnas, Muhammad Shafwan; Nugraha, Dibyo Restu (Faculty of Psychology, Universitas Gadjah Mada, 2024)
Employees are expected to achieve optimal task performance. Therefore, workplace well-being is crucial for employees to enhance their work engagement and, consequently, reach high task performance. This study aims to examine the mediating role of work engagement in the relationship between workplace well-being and task performance. Utilizing a quantitative survey method, the research involved 310 employees selected through convenience sampling. The instruments used in the study included scales for workplace well-being, work engagement, and task performance. The results revealed that work engagement significantly mediates the effect of workplace well-being on employee task performance. These findings provide a basis for developing theoretical models of task performance and formulating training programs to enhance employee task performance, particularly in the field of applied psychology.